Alicia en el país de las maravillas ; A través del espejo - Carroll, Lewis, 1832-1898; Torres Oliver, Francisco; Tenniel, John, 1820-1914; Carroll, Lewis, 1832-1898.; Carroll, Lewis, 1832-1898.; Carroll, Lewis, 1832-1898.; Carroll, Lewis, 1832-1898. (Tres Cantos, Madrid, España : Ediciones Akal, S.A., 2012)
By falling down a rabbit hole and stepping through a mirror, Alice experiences unusual adventures with a variety of nonsensical characters.
Online resource; title from ePub title page (Digitalia, viewed January 9, 2017).
Keywords: Alice -- (Fictitious character from Carroll) -- Juvenile fiction; Electronic books; Fantasy fiction; Fiction